Matej Šurc. Patriotism for Sale: How Independent Slovenia Fell Foul of Crooked Arms Dealers. Translated by Roman Vučajnk. Ljubljana: Sanje, 2018. - Charney, Noah (Slovene Studies Journal, 2019)
abstract